KELIMPAHAN JENIS SATWA LIAR DENGAN MENGGUNAKAN KAMERA JEBAKAN DI CAGAR ALAM GUNUNG AMBANG - Pongantung Fandy; Johny S. Tasirin; Hard N, Pollo (Universitas Sam Ratulangi, 2019)
ABSTRACT Wildlife is a form of natural wealth and biodiversity of natural resources. Habitat destruction and human activities, factors that influence the decline in wildlife populations, are evident in Mt. Ambang Nature Reserve. The purpose of this study was to determine the richness of species, level of encounter, and abundance of wild species by using camera traps in the Mt. Ambang Nature Reserve. Data analysis is based on species, the number of photos, the number of individuals and the number of active days of cameras. The results shows that there were 5 wildlife species i.e. Ailurops ursinus (Phalangeridae), Gallus gallus (Phasianidae), Macaca nigra (Cercopithecidae), Macrogalidia musschenbroekii (Viverridae), Sus celebensis (Suidae). The encounter rate (ER) is dominated by M. nigra (ER 0.70 photos/day) and followed by G. gallus, M. musschenbroekii, S. celebensis, A. ursinus (ER 0.10, 0.06, 0.03, 0.01 photos/day, consecutively). The wildlife species with the highest abudance is M. nigra (KR 63,4). It is followed by G. gallus, M. musschenbroekii, A. ursinus, and S. celebensis (KR 19.5%, 9.7%, 4.8%, 2.4%, consecutively). Keywords: wildlife, camera traps, level of encounter, abundance